The Effect of Corporate Social Responsibility on Profit Management Registered in Indonesian Stock Exchange - Sukiantono Tang; Ristiani Hastuty (Universitas Medan Area, 2022)
In the present day many companies have implemented social responsibility programs with the aim of attracting the attention of investors. With social responsibility activities, the company can minimize the act of manipulating a company report. Agency theory is related to the delivery of company information from managers to the company principal. The benefits that will be provided to the company are contributing company knowledge to social responsibility activities where these activities can trigger activities from profit management. The data obtained as many as 352 samples of companies have financial statements and sustainability reports that have been published by the IDX in the range of 2017 - 2021 using panel data regression in determining research data analysis. Based on the results of this study, it proves that there is no significant influence of corporate social responsibility which consists of 7 elements, including corporate governance, human rights, labor relations, the environment, fair practices, measures of consumer expectations and community involvement in profit management in companies listed on the IDX.